Extracellular vesicles and miRNA-based therapies in triple-negative breast cancer: advances and clinical perspectives - Rezende, Caroline Patini de; Alves, Debora de Lima; Chuffa, Luiz Gustavo de Almeida [UNESP]; Zuccari, Debora Aparecida Pires de Campos (Oae Publishing Inc, 2025)
Triple-negative breast cancer (TNBC) is one of the most aggressive and challenging subtypes for treatment, due to the lack of hormone receptors and the human epidermal growth factor receptor 2 (HER2) protein. The identification of new molecular targets is important for the development of targeted and specific therapies for TNBC patients. MicroRNAs (miRNAs) have emerged as promising molecular targets, being involved in cellular processes such as cell survival, apoptosis, differentiation, carcinogenesis, and metastasis. Extracellular vesicles (EVs) have gained prominence in areas such as drug delivery, immune modulation, biomarkers for diagnosis and prognosis, and therapeutics, due to their use as vehicles for the delivery of miRNAs, regulation of gene expression, and development of combined therapeutic strategies. In particular, mesenchymal stem cell-derived EVs (MSC- derived EVs) can transfer proteins, mRNAs/miRNAs, or DNA molecules and are being considered safer treatment options due to their inability to directly form tumors and contain lower amounts of membrane proteins such as MHC molecules. Numerous studies have highlighted the role of miRNAs in EVs in TNBC tumorigenesis, with a focus on diagnosis, prognosis, treatment selection, and monitoring. However, the development of therapies with EVs, especially MSC-derived EVs, is still in its infancy. Therefore, the aim of this review is to address new therapeutic strategies based on the delivery of miRNAs through EVs, with a focus on MSC-derived EVs, for the treatment of TNBC as an innovative therapy in oncology.
Keywords: Extracellular vesicles (EVs); miRNAs; EVs-miRNAs therapies; mesenchymal stem cells (MSCs); triple-negative breast cancer (TNBC)